Assessment of Attitude of off-Campus Living Female Students in Bonga College of Teachers Education - Ware, Yohannes Abebe (International Journal of Formal Sciences: Current and Future Research Trends, 2019)
The purpose of this study was examining the attitudes of off-campus living female students of Bonga College of Teachers Education. In this study a descriptive survey method was employed. Information was collected through a questionnaire from 107 third year female students. Quantitative data were analyzed using percentage, mean and descriptive statements as well as graphs. The analysis of the results shows that their attitude towards off campus living is almost negative.